Child Marriage in Indonesia Based on Maqasid al-Shariah and the 2019 Marriage Law - Imam Anshori; Muhammad Kholid Abdullah; Suyud Arif; Syarifah Gustiawati Mukri (Universitas Ibn Khaldun, 2025)
This study examines the practice of child marriage from the perspective of maqasid sharia. It analyzes it against the provisions of Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage in Indonesia. The main focus of this study is to review the extent to which the minimum age limit for marriage in the law aligns with the objectives of Islamic law, particularly in the context of hifz al-nasl (protecting offspring). In maqasid sharia, marriage is not only seen from the legal aspect of age, but also from the perspective of physical and psychological readiness and moral responsibility that support the realization of a healthy and beneficial family. This study employs a qualitative approach, utilizing a library research method to analyze classical sources in Islamic literature, the opinions of scholars, and applicable laws and regulations in Indonesia. The results show that although Islamic law does not explicitly stipulate an age limit, maqasid sharia encourages the protection of children and offspring by emphasizing the importance of readiness (al-ba'ah) before marriage. Meanwhile, Law No. 16 of 2019 sets the minimum age for marriage as a preventive measure against the negative impacts of early marriage, which is in line with the spirit of maqasid syari'ah in protecting one's nasab. It is hoped that this study can contribute to strengthening the understanding of the harmonization between Islamic law and Indonesian positive law and become a basis for thinking in formulating legal policies that support child protection and the sustainability of future generations.